2009
DOI: 10.1159/000210835
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus Subgenotypes and Basal Core Promoter, Precore Variants in Patients with Acute Hepatitis B in Central Vietnam

Abstract: Objective: Hepatitis B virus (HBV) has been classified into 8 genotypes that have different geographic distributions. The clinical outcomes of acute hepatitis are dependent on genotype. The aim of this study was to investigate the distribution of HBV subgenotypes and basal core promoter (BCP)/precore (PC) regions in acute hepatitis patients in Central Vietnam to clarify the distributions and the clinical and virological differences. Methods: 27 patients with acute hepatitis B were studied. HBV subgenotypes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…HBV genotype B and C are the two common genotypes in China [2527] and Vietnam [28,29], a neighboring country of Southern Guangxi, where more than 80% of subjects have genotypes B or C. A previous study in Guangxi area reported 100% of genotype C in 20 asymptomatic HBV carriers [30], which was higher but still comparable to 84.2% of genotype C in our controls.…”
Section: Discussionsupporting
confidence: 47%
“…HBV genotype B and C are the two common genotypes in China [2527] and Vietnam [28,29], a neighboring country of Southern Guangxi, where more than 80% of subjects have genotypes B or C. A previous study in Guangxi area reported 100% of genotype C in 20 asymptomatic HBV carriers [30], which was higher but still comparable to 84.2% of genotype C in our controls.…”
Section: Discussionsupporting
confidence: 47%
“…Our study among the general population found that the most popular HBV genotype is B (75.3%), followed by C (11.7%). Comparable HBV genotype distribution of genotypes B and C were also observed in Vietnam . However, genotype C was reported to predominate over genotype B .…”
Section: Discussionmentioning
confidence: 75%
“…Comparable HBV genotype distribution of genotypes B and C were also observed in Vietnam. 14,15 However, genotype C was reported to predominate over genotype B. 16,17 These conflicts may be due to different study populations; genotype B was common among asymptomatic HBV infected cases, whereas genotype C was prominent in patients with liver cirrhosis and HCC.…”
Section: W E Found In This Survey That Prevalence Ofmentioning
confidence: 99%
“…Recent studies have identified several HBV variants and mutants playing an important role in disease pathogenesis, immune escape, and resistance to antiviral therapy[18,19]. HBV variants such as A1896 occur under the selective pressures from the host's immune system and from viral factors [20,21], whereas HBV mutants, such as rtI204 and rtV204, usually occur secondary to exogenous factors such as lamivudine and associate with a specific phenotype[12,22].…”
Section: Discussionmentioning
confidence: 99%